عرض البيانات المالية وفق مشروع عصرنة نظام المحاسبة العمومية بالجزائر ومدى توافقها مع معايير المحاسبة الدولية للقطاع العام Ipsas - حسياني, عبد الحميد; بوعبانة, فتيحة (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى إبراز دور وأهمية معايير المحاسبة الدولية للقطاع العام في عصرنة نظام المحاسبة العمومية، وعرض المعيار الجزائري للقطاع العام رقم 1 "عرض البيانات المالية" ودراسة مقارنة بينه وبين المرجع الدولي. وخلصت الدراسة في هذا الشأن أن هناك تطابق شبه تام بين المعيار الجزائري والدولي، وتم ملاحظة أن المعيار الدولي أكثر تفصيلا من المعيار الجزائري وتأكيد أن جميع العناصر المتضمنة في المعايير الجزائرية قد نصت عليها المعايير الدولية وهناك اختلاف في بعض المصطلحات فقط، كما أن عرض بيانات مالية وفق المعيار الجزائري والدولي يوفر مزيدا من الإفصاح، الشفافية، المساءلة المالية وقابلية المقارنة. This study aims to highlight the role and importance of international public sector accounting standards in modernizing the public accounting system, and present the Algerian public sector standard No. 1 "Presentation of financial statements" and a comparative study between it and the international reference. The study concluded in this regard that there is a near-perfect match between the Algerian and international standards, and it was noted that the international standard is more detailed than the Algerian standard and confirmed that all elements included in the Algerian standard have been stipulated in the international standard and there is a difference in some terms only, and that the presentation of financial data According to the Algerian and international standards, it provides more disclosure, transparency, financial accountability and comparability.
Presenting the financial statements according to the modernization of the public accounting system project and its compatibility with the international public (IPSAS) sector accounting standards
مقال
Keywords: معايير المحاسبة الدولية للقطاع العام ; مشروع عصرنة نظام المحاسبة العمومية ; معيار المحاسبة للقطاع العام رقم 1 ; IPSAS